780MPa-grade low-cost nano precipitation type high-hole-expansion steel and production method thereof

Through low C, low Mn, Ti-B composite microalloy composition and precise process flow, 780MPa grade low-cost nano-precipitation high-pore expansion steel was prepared, solving the problem of high costs and achieving improvements in mechanical properties and pore expansion performance , suitable for automotive parts, with broad market application prospects.

CN119194265APending Publication Date: 2024-12-27PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484028.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing 780MPa grade hot rolled high-strength high-pore expansion steel has high alloy costs and production costs.

Method used

The composition design of low C, low Mn, Ti-B composite microalloy is prepared through precise heating, rapid cooling in the front section, and medium and high temperature coiling technology. The microstructure is Ferrite + nano-precipitation phase controls chemical composition and process flow to reduce costs.

Benefits of technology

It has achieved low-cost 780MPa grade high-pore expansion steel, with good mechanical properties and pore expansion performance, suitable for automotive chassis and other components, and has broad market application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194265A_ABST
    Figure CN119194265A_ABST
Patent Text Reader

Abstract

The invention discloses 780MPa-grade low-cost nano precipitation type high-hole-expansion steel and a production method thereof, and belongs to the technical field of metallurgy. The chambering steel comprises, by mass, 0.015%-0.050% of C, smaller than or equal to 0.05% of Si, 1.30%-1.70% of Mn, smaller than or equal to 0.015% of P, smaller than or equal to 0.002% of S, 0.10%-0.20% of Cr, 0.080%-0.110% of Ti, 0.0015%-0.0040% of B, 0.010%-0.050% of Als, smaller than or equal to 0.0030% of N, smaller than or equal to 0.005% of C (Ti-3. 42 * N-1. 5 * S)-0.16 * Cr and the balance Fe and impurities. The 780MPa-grade low-cost nano precipitation type high-hole-expansion steel with good mechanical property and hole expansion property is obtained through the production method of smelting, heating, rough rolling, finish rolling, laminar cooling and coiling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a 780MPa-level low-cost nano-precipitation type high-hole expansion steel and a production method thereof. Background Art

[0002] In order to reduce the weight of automobiles, reduce fuel consumption and improve vehicle safety, in recent years, many new steel research and development plans have focused on the development of advanced high strength steel (AHSS) with good formability. There are many types of AHSS steel, such as ferrite / martensite dual phase (Ferrite / Martensite Dual Phase, FMDP) steel, ferrite / bainite dual phase (Ferrite / Bainite Dual Phase) steel, transformation induced plasticity (TRAP) steel, twinning induced plasticity (TWIP) steel, complex phase (CP) steel, martensite (M) steel, quenching and partitioning (Q&P) steel and hot formed (HF) steel.

[0003] In addition to solid solution, grain refinement, precipitation and other strengthening methods, AHSS steel also has phase transformation strengthening, which is not available in ordinary high-strength steel and is one of the main strengthening methods of AHSS steel. Compared with ordinary high-strength steel, AHSS steel has the advantages of good formability, high energy absorption rate, good anti-collision dent performance, bake hardening performance, yield strength, high work hardening rate and good fatigue performance, and is increasingly showing its good application scenarios in the automotive industry.

[0004] Hot-rolled high-strength steel plates are used to make automobile chassis, wheels and other automobile running parts, and are one of the important and effective ways to achieve vehicle weight reduction. Automobile chassis parts are not exposed, and although the surface quality requirements of steel plates are not very strict, due to their complex shapes, the main forming methods include: stretching flanging, bending, hole expansion and electric spark forming, etc. These forming methods have high requirements on the formability of steel plates, especially the extended flange performance.

[0005] When forming complex automotive parts (such as automobile chassis, wheel rims and spokes, etc.), traditional FMDP steel has a two-phase (F+M) interface with a large difference in deformation capacity. It is easy to crack at the opening during the forming process, and the extended flange forming performance is not good enough. Especially after flash welding, martensite tempering and softening are easy to occur in the heat affected zone (HAZ). At the same time, the fatigue strength is low, so it cannot meet the forming requirements.

[0006] FBDP steel is also called stretch-flangeable (SF) steel or high hole-expansion (HEE) steel. When the bainite content is 10% to 20%, it has very good forming properties, especially stretch flange performance. Compared with HSLA and FMDP steels, the main advantage of FBDP steel is that it improves the shear edge ductility, takes into account the contradiction and balance between strength and ductility, and has good welding, fatigue and hole expansion performance, which has advantages that general materials cannot match; the hardness of the heat-affected zone of FBDP steel after flash welding is higher than that of the base metal, and there will be no softening phenomenon during subsequent processing. At the same time, the steel has good light-fatigue performance. Compared with HSLA steel of the same strength level, FBDP steel has higher strain hardening index (n value) and total elongation, so FBDP steel is more suitable for stamping parts with high requirements and good elongation performance, such as automobile chassis.

[0007] In the 1990s, the United States, Japan and other countries successively developed hot-rolled FB steel plates with high hole expansion performance of 440-780MPa. The hole expansion rate was 70%-131%. It was mainly used in automobile chassis, wheels and other parts with good formability, especially flanging performance. It contains more precious alloy elements such as Cr, Nb, Ti, V and Mo. Although ferrite / bainite dual-phase structure can be obtained under low cooling rate conditions, its cost is relatively high.

[0008] The Chinese invention patent with publication number CN103602895B discloses a 780MPa grade high hole expansion steel plate and a manufacturing method thereof, wherein the mass percentage content is: C 0.02% to 0.1%, Si 0.5% to 1.5%, Mn 1.5% to 2.2%, P≤0.02%, S≤0.003%, Al 0.020% to 0.060%, N≤0.0050%, Nb 0.02% to 0.06%, Ti 0.05% to 0.15%, Ca<0.0050%, Mg0 to 0.005%, and the rest is iron and unavoidable impurities; and at the same time, the following relationship needs to be satisfied: ([C]-12 / 48×([Ti]-48 / 14×[N])-12 / 93×[Nb])≥0.005. The thickness of the steel plate is 2.0mm to 5.0mm, including converter steelmaking, RH vacuum degassing of molten iron, LF furnace desulfurization, continuous casting, slab heating, hot rolling, cooling, pickling and other production processes; the slab heating temperature is 1200℃ to 1260℃, the final rolling temperature is 860℃ to 930℃, a one-stage cooling method is adopted, the cooling rate is greater than 20℃ / s, the coiling temperature is 450℃ to 550℃, the thickness tensile strength is above 780MPa, and the hole expansion rate is above 50%. The invention aims to obtain a single ferrite structure, but since a certain amount of carbon still exists in the form of solid solution, it is very easy to form cementite and segregate at the grain boundary, which is not conducive to the hole expansion performance; in addition, since the coiling temperature is between 450℃ and 550℃, the precipitation of TiC is suppressed, and it mainly exists in the form of solid solution, which is a waste of alloy resources for steel grades.

[0009] The Chinese invention patent with publication number CN105154769B discloses a 780MPa grade hot-rolled high-strength high-hole expansion steel and a manufacturing method thereof, wherein the mass percentage content is: 0.03%≤C≤0.07%, Si≤0.2%, 0.02%≤Al≤0.05%, 1.0%≤Mn≤2.0%, P≤0.02%, S≤0.005%, N≤0.0050%, 0.08%≤Ti≤0.20%, 0.15%≤Mo≤0.25%, O≤0.003%, and 0.25≤Ti / Mo≤1.5, 0.03%≤(Ti-3.42N) / 4+Mo / 8≤0.07%, and the rest is iron and unavoidable impurities. The high-strength high-hole expansion steel of the present invention is manufactured through smelting, casting, high-temperature heating, hot rolling, and coiling processes, and its yield strength is ≥750MPa, tensile strength is ≥780MPa, elongation is ≥20%, and the hole expansion rate is ≥70% when the thickness is 3-6mm. Although the invention can obtain a single ferrite structure, the proportion of large-particle liquid TiN increases sharply when the Ti and N content is too high, resulting in reduced plasticity and hole expansion performance of the product; the high-temperature coiling process is used, resulting in the enlargement of the carbide precipitation phase size, and the coarsened precipitation phase will cause the material's hole expansion performance to deteriorate; in addition, the high addition amount of the precious element Mo leads to excessively high production costs of the material.

[0010] The Chinese invention patent with publication number CN114107789B discloses a 780MPa grade high surface, high performance, stability and ultra-high hole expansion steel and a manufacturing method thereof, wherein the mass percentages thereof are: C 0.03% to 0.08%, Si ≤ 0.2%, Mn 0.5% to 2.0%, P ≤ 0.02%, S ≤ 0.003%, Al 0.01% to 0.08%, N ≤ 0.004%, Ti 0.05% to 0.20%, Mo 0.1% to 0.5%, Mg ≤ 0.005%, O ≤ 0.0030%, Nb ≤ 0.06%, V ≤ 0.05%, Cu ≤ 0.5%, Ni ≤ 0.5%, Cr ≤ 0.5%, B ≤ 0.001%, and Ca ≤ 0.005%. The ultra-high hole expansion steel described in the invention has good organizational uniformity, performance uniformity and excellent strength, plasticity, and ultra-high hole expansion rate matching. Its yield strength is ≥750MPa, tensile strength is ≥780MPa, and elongation A 50 ≥15%, hole expansion rate ≥70%; bainite and bainitic ferrite are obtained through low-temperature coiling + hood annealing process, but the alloy cost and process cost of this product are much higher than those of conventional products, and the low-temperature coiling process after rolling will inevitably lead to poor steel coil shape.

[0011] The Chinese invention patent with publication number CN114107792B discloses a 780MPa grade high surface ultra-high hole expansion steel and a manufacturing method thereof, wherein the mass percentage content is: C0.03% to 0.08%, Si≤0.2%, Mn0.5% to 2.0%, P≤0.02%, S≤0.003%, Al0.01% to 0.08%, N≤0.004%, Ti0.05% to 0.20%, Mo0.1% to 0.5%, Mg≤0.005%, O≤0.0030%, Nb≤0.06%, V≤0.05%, Cu≤0.5%, Ni≤0.5%, Cr≤0.5%, B≤0.001%, and Ca≤0.005%. The ultra-high hole expansion steel described in the invention has good organizational uniformity, performance uniformity and excellent strength, plasticity, and ultra-high hole expansion rate matching. Its yield strength is ≥700MPa, tensile strength is ≥780MPa, and elongation A 50 ≥17%, hole expansion rate ≥80%. The product is rapidly cooled after rolling, coiled between 550℃~650℃ and slowly cooled to obtain irregular ferrite, nano-carbides in ferrite crystals and very little pearlite. Although ultra-high hole expansion performance is obtained, the alloy cost of this product is much higher than that of conventional products. Summary of the invention

[0012] The technical problem to be solved by the present invention is the high alloy cost and production cost of the existing 780MPa grade hot-rolled high-strength high-hole expansion steel.

[0013] The technical solution adopted by the present invention to solve its technical problem is:

[0014] In the first aspect, the present invention provides a 780MPa grade low-cost nano-precipitation type high hole expansion steel, whose chemical composition is as follows by mass percentage: 0.015≤C≤0.050%, Si≤0.05%, 1.30%≤Mn≤1.70%, P≤0.015%, S≤0.002%, 0.10≤Cr≤0.20%, 0.080%≤Ti≤0.110%, 0.0015%≤B≤0.0040%, 0.010%≤Als≤0.050%, N≤0.0030%, and C-(Ti-3.42×N-1.5×S)-0.16×Cr≤0.005%, and the balance is Fe and unavoidable impurities.

[0015] The microstructure of the high hole expansion steel is ferrite + nano-precipitation phase.

[0016] Furthermore, the microstructure of the high hole expansion steel is acicular ferrite+quasi-polygonal ferrite+nano precipitate phase.

[0017] The R of the above high hole expansion steel eL ≥650MPa, R m≥780MPa, A 50 ≥20%, hole expansion rate λ≥70%.

[0018] The thickness specification of the above-mentioned high hole expansion steel is 2.0 to 6.0 mm.

[0019] In a second aspect, the present invention provides a method for producing the above-mentioned 780MPa-grade low-cost nano-precipitation type high hole expansion steel, the production method comprising smelting, heating, rough rolling, finish rolling, laminar cooling and coiling steps, wherein:

[0020] Heating process: The continuous casting slab heating temperature is 1250±15℃, the heating time is 200~300min, and the holding time is ≥30min;

[0021] Laminar cooling process: adopt the front-stage rapid cooling method, the laminar cooling rate is ≥70℃ / s, and the midpoint temperature is 620~650℃;

[0022] Coiling process: The coiling temperature is 590-620℃. After coiling, it is slowly cooled in the cooling pit for more than 48 hours and then cooled to room temperature.

[0023] In the above production method, the smelting process includes molten iron desulfurization, converter, first RH vacuum treatment, LF refining, second RH vacuum treatment, and slab continuous casting.

[0024] Furthermore, high carbon ferromanganese is used for manganese matching in the converter process without decarburization; decarburization is carried out during the first RH vacuum treatment; quantitative and precise carbon addition is carried out in LF; and low nitrogen sponge titanium is used for reduction alloying during the second RH vacuum treatment.

[0025] In the above production method, the thickness of the intermediate billet at the rough rolling outlet is controlled to be 35 to 50 mm in the rough rolling process.

[0026] Furthermore, when the intermediate billet thickness is ≤45 mm, the intermediate billet is coiled and descaled by a hot coil box.

[0027] In the above production method, the finishing rolling inlet temperature is controlled to be 1030-1080°C and the final rolling temperature is controlled to be 860-900°C in the finishing rolling process.

[0028] The beneficial effects of the present invention are as follows: first, the present invention adopts a composition design of low C, low Mn, and Ti-B composite microalloying, does not add precious alloys, reduces the alloy cost of steel, and achieves economy from the material aspect. Secondly, the present invention specifically designs an easy-to-produce process flow, and obtains 780MPa-level low-cost nano-precipitation high-hole expansion steel with good mechanical properties and hole expansion performance through precise heating, rapid cooling in the front section, and medium-high temperature coiling.

[0029] The steel obtained by the preparation method of the present invention is widely used in manufacturing swing arms, longitudinal arms and other parts with flanging and hole expansion requirements, and is widely used in the lightweight design of new energy vehicles and fuel vehicles, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The microstructure of the high hole expansion steel prepared in Example 2-2;

[0031] Figure 2 The microstructure of the high hole expansion steel prepared in Comparative Example 1-1;

[0032] Figure 3 The microstructure of the high hole expansion steel prepared in Comparative Example 2-1;

[0033] Figure 4 The microstructure of the high hole expansion steel prepared in Comparative Example 2-2;

[0034] Figure 5 The surface morphology of the high hole expansion steel prepared in Example 2-2;

[0035] Figure 6 This is the surface morphology of the high hole expansion steel prepared in Comparative Example 1-1. DETAILED DESCRIPTION

[0036] The technical solution of the present invention can be specifically implemented in the following manner.

[0037] 780MPa grade low-cost nano-precipitation type high hole expansion steel, whose chemical composition is as follows by mass percentage: 0.015≤C≤0.050%, Si≤0.05%, 1.30%≤Mn≤1.70%, P≤0.015%, S≤0.002%, 0.10≤Cr≤0.20%, 0.080%≤Ti≤0.110%, 0.0015%≤B≤0.0040%, 0.010%≤Als≤0.050%, N≤0.0030%, and C-(Ti-3.42×N-1.5×S)-0.16×Cr≤0.005%, and the balance is Fe and unavoidable impurities.

[0038] The chemical composition design principle of the 780MPa grade low-cost nano-precipitation type high pore expansion steel of the present invention is explained.

[0039] (1) C: It must have a certain content to promote the formation of carbide strengthening phase, thereby ensuring the strength level of the steel strip. When its content is too high, the precipitated carbide particles will increase, which is not conducive to the hole expansion performance of the steel plate; when its content is too low, the strength cannot meet the design requirements. The present invention controls the C content between 0.015% and 0.050%, and forms a nano-TiC precipitation phase by adding Ti, fixes free C, reduces the Fe3C content, and achieves the purpose of strengthening the ferrite matrix.

[0040] (2) Si: It has a solid solution strengthening effect, which can simultaneously improve the strength and elongation of the steel strip and improve the formability of the steel strip. Generally, the silicon content should not be less than 0.30%. However, when the Si content is high, Fe2SiO4 red rust is easily generated on the surface of the steel strip, which is difficult to remove during pickling. In order to improve the surface quality of the steel strip and reduce the difficulty of industrial production, the present invention designs a Si-free composition scheme, that is, Si≤0.05%.

[0041] (3) Mn: It is a solid solution strengthening element. According to the strength requirements of this steel grade, when the content is too low, the strength will not meet the design requirements; when the content is too high, the proportion of pearlite will increase, and high Mn content will easily lead to Mn component segregation in the ingot, which is one of the main reasons for the appearance of banded structure in the steel strip, and the banded structure will cause the hole expansion performance of the steel strip to drop sharply. At the same time, for carbon manganese steel, the interaction between C and Mn has a certain influence on the formation and distribution of pearlite structure. When the content of both is too high, coarse pearlite and banded structure are easily generated. Therefore, under the premise that the strength meets the design requirements, the C content and Mn content are designed to be as low as possible. The Mn content of the present invention is controlled at 1.30% to 1.70%.

[0042] (4) P: As the strongest element for strengthening ferrite, it has strong solid solution strengthening and cold work hardening effects. When used as an alloying element, it can improve the strength and atmospheric corrosion resistance of the steel strip. However, when the content is too high, the cold stamping performance of the steel strip will drop sharply. At the same time, there will be segregation of the components of the continuous casting slab, causing uneven structure, increased temper brittleness, and significantly reduced plasticity and toughness of the steel strip, so that the steel strip will become "cold brittle" and brittle during cold working. The present invention controls the content to be below 0.015%.

[0043] (5) S: It is an impurity element in steel and is easy to form MnS in steel. The amount and shape of sulfides in steel directly affect the hole expansion performance of the steel strip. In particular, strip-shaped sulfide inclusions are prone to cracking during deformation. Therefore, when designing the chemical composition, the S content must be reduced, that is, below 0.003%.

[0044] (6) Ti: It plays the role of precipitation strengthening and grain refinement strengthening in steel. Nano-scale TiC, TiN and Ti(C,N) are dispersed in the fine ferrite matrix. At the same time, Ti inhibits the coarsening of the original austenite structure during the slab reheating process, which is beneficial to grain refinement and thus improves the hole expansion performance. The Ti content of the present invention is controlled at 0.080% to 0.110%.

[0045] (7) Cr: It can delay the transformation of pearlite, significantly improve the hardenability of steel, facilitate the formation of acicular ferrite and granular bainite, and refine the structure to achieve a strengthening effect. If the Cr content is too high, the processing and formability of the material will deteriorate. The principle of selecting the Cr content is to promote the formation of acicular ferrite and granular bainite and avoid the formation of martensite structure which has an adverse effect on elongation. Therefore, the Cr content of the present invention is in the range of 0.10% to 0.20%.

[0046] (8) Al: Its basic function in the present invention is deoxidation during the steelmaking process. The Als content in steel is generally less than 0.010%; at the same time, if the Als content exceeds 0.060%, its grain refinement effect is weakened. The present invention controls the Als content to 0.010% to 0.050%.

[0047] (9) N: It can combine with alloy elements to produce non-metallic inclusions, which reduces the effect of alloy elements and is considered a harmful element. Under controlled rolling and controlled cooling conditions, N, C and Ti combine to form a nano-precipitated phase Ti (C, N). The present invention requires N≤0.0030%.

[0048] (10) B: Adding B element to steel can greatly improve the hardenability of steel and is conducive to obtaining martensite structure. Considering that the structure expected to be obtained in the hot rolling stage of the present invention is ferrite rather than martensite, the present invention adopts medium-high coiling temperature control after rolling. In order to obtain a higher proportion of needle-shaped quasi-polygonal ferrite structure, a certain amount of B element needs to be added. In addition, in order to avoid the addition of B element to induce the generation of large-sized martensitic components and reduce toughness, the coiling temperature should not be too low.

[0049] The production method of 780MPa grade low-cost nano-precipitation type high hole expansion steel includes smelting, heating, rough rolling, finish rolling, laminar cooling and coiling processes.

[0050] The production method of the 780MPa grade low-cost nano-precipitation type high hole expansion steel of the present invention is described.

[0051] (1) Smelting process: The smelting process includes "hot iron desulfurization → converter → RH vacuum treatment → LF refining → RH vacuum treatment → slab continuous casting" and other processes: high carbon ferromanganese is used for manganese matching in the converter process without decarburization; decarburization is carried out during the first RH vacuum treatment, and then quantitative and precise carbon addition is carried out in LF; low nitrogen sponge titanium must be used for alloying in the second RH process. This technology can use relatively cheap high carbon ferromanganese alloy, reduce the consumption of aluminum deoxidizer, and greatly reduce iron loss and oxygen content in molten steel. The chemical composition of the ingot is controlled according to the chemical composition of 780MPa low-cost nano-precipitation high-hole expansion steel.

[0052] (2) Heating process: To ensure that alloy elements such as Ti, Mn, Cr, and B are fully dissolved, the heating temperature of the continuous casting slab is controlled to be 1250±15℃, and the heating time is 200-300min, of which the holding time is ≥30min.

[0053] (3) Rough rolling process: The thickness of the intermediate billet at the rough rolling outlet is controlled to be 35-50 mm.

[0054] (4) Hot coil box: When the intermediate billet thickness is ≤45mm, the intermediate billet is coiled and scaled.

[0055] (5) Finishing rolling process: The finishing rolling inlet temperature is controlled at 1030-1080°C and the final rolling temperature is controlled at 860-900°C.

[0056] (6) Laminar cooling process: After finishing rolling, the steel strip adopts the front-stage rapid cooling method, the laminar cooling rate is ≥70℃ / s, and the midpoint temperature is 620~650℃.

[0057] (7) Coiling temperature: To ensure that there are enough nano-sized TiC, TiN and Ti(C,N), and under the action of strong hardenability elements Cr and B, the coiling temperature is controlled at 590-620°C to obtain a stable acicular ferrite structure. The steel is then coiled and slowly cooled for more than 48 hours before being cooled to room temperature.

[0058] The 780MPa grade low-cost nano-precipitation type high hole expansion steel prepared according to the above alloy chemical composition and production method of the present invention has a thickness specification of 2.0-6.0mm; its microstructure is ferrite + nano-precipitation phase; mechanical properties: R eL ≥650MPa, R m ≥780MPa, A 50 ≥20%; Hole expansion performance: Hole expansion rate λ≥70%.

[0059] The technical solution and effects of the present invention are further illustrated below through practical examples.

[0060] Example

[0061] In order to further understand the present invention, three groups of Examples 1 to 3 using the chemical composition of the present invention and a group of Comparative Example 1 using the chemical composition of existing steel of the same grade are provided. The specific chemical compositions are shown in Table 1, and the remainder is Fe and unavoidable impurities.

[0062] Table 1 Chemical composition (by mass percentage, %)

[0063]

[0064]

[0065] The ingot is smelted according to the chemical composition described in Table 1, and then the finished steel is prepared through the ingot heating, rough rolling, finish rolling, laminar cooling and coiling processes. The key process parameters in the preparation method are shown in Table 2.

[0066] Table 2 Process parameters

[0067]

[0068] Figure 1 The microstructure of the finished steel obtained in Example 2-2 is as follows: Figure 1 It can be seen that the microstructure of the finished steel obtained by adopting the chemical composition and production method of the present invention is acicular ferrite + quasi-polygonal ferrite + nano-precipitated phase; Figure 5 The appearance of the finished steel obtained in Example 2-2 is as follows: Figure 5 It can be seen that there is no red rust defect on the surface of the product.

[0069] Figure 2 The microstructure of the finished steel obtained in Comparative Example 1-1 is as follows: Figure 2 It can be seen that the microstructure of the steel obtained in Comparative Example 1-1 is lath bainite + quasi-polygonal ferrite + pearlite; Figure 6 The appearance of the finished steel obtained in Comparative Example 1-1 is as follows: Figure 6 It can be seen that red rust defects are prone to appear on the product surface.

[0070] Figure 3 The microstructure of the finished steel obtained in Comparative Example 2-1 is as follows: Figure 3 It can be seen that the microstructure of the steel obtained in Comparative Example 2-1 is lath bainite + acicular ferrite + a small amount of precipitation phase.

[0071] Figure 4 The microstructure of the finished steel obtained in Comparative Example 2-2 is as follows: Figure 4 It can be seen that the microstructure of the steel obtained in Comparative Example 2-2 is quasi-polygonal ferrite + precipitation phase.

[0072] The mechanical properties of the finished steel products obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the results are shown in Table 3.

[0073] Table 3 Mechanical properties

[0074]

[0075]

Claims

1. 780MPa low-cost nano-precipitation high-hole expansion steel, characterized by: Its chemical composition by mass percentage is: 0.015≤C≤0.050%, Si≤0.05%, 1.30%≤Mn≤1.70%, P≤0.015%, S≤0.002%, 0.10≤Cr≤0.20%, 0.080%≤Ti≤0.110%, 0.0015%≤B≤0.0040%, 0.010%≤Als≤0.050%, N≤0.0030%, and C-(Ti-3.42×N-1.5×S)-0.16×Cr≤0.005%, and the balance is Fe and unavoidable impurities.

2. The 780MPa low-cost nano-precipitation high hole expansion steel according to claim 1, characterized in that: The microstructure of the high hole expansion steel is acicular ferrite+quasi-polygonal ferrite+nano precipitate phase.

3. The 780MPa low-cost nano-precipitation type high hole expansion steel according to claim 1, characterized in that: The R of the high hole expansion steel eL ≥650MPa, R m ≥780MPa, A 50 ≥20%, hole expansion rate λ≥70%.

4. The 780MPa low-cost nano-precipitation high hole expansion steel according to claim 1, characterized in that: The thickness specification of the high hole expansion steel is 2.0 to 6.0 mm.

5. The method for producing 780MPa grade low-cost nano-precipitation type high hole expansion steel according to any one of claims 1 to 4, characterized in that: The production method comprises smelting, heating, rough rolling, finishing rolling, laminar cooling and coiling steps, wherein: Heating process: The continuous casting slab heating temperature is 1250±15℃, the heating time is 200~300min, and the holding time is ≥30min; Laminar cooling process: adopt the front-stage rapid cooling method, the laminar cooling rate is ≥70℃ / s, and the midpoint temperature is 620~650℃; Coiling process: The coiling temperature is 590-620℃. After coiling, it is slowly cooled in the cooling pit for more than 48 hours and then cooled to room temperature.

6. The method for producing 780MPa grade low-cost nano-precipitation type high hole expansion steel according to claim 5, characterized in that: The smelting process includes molten iron desulfurization, converter, first RH vacuum treatment, LF refining, second RH vacuum treatment, and slab continuous casting.

7. The method for producing 780MPa grade low-cost nano-precipitation type high hole expansion steel according to claim 6, characterized in that: In the converter process, high carbon ferromanganese is used for manganese matching without decarburization; decarburization is carried out during the first RH vacuum treatment; quantitative and precise carbon addition is carried out in LF; and low nitrogen sponge titanium is used for reduction alloying during the second RH vacuum treatment.

8. The method for producing 780MPa grade low-cost nano-precipitation type high hole expansion steel according to claim 5, characterized in that: In the rough rolling process, the thickness of the intermediate billet at the rough rolling outlet is controlled to be 35 to 50 mm.

9. The method for producing 780MPa grade low-cost nano-precipitation type high hole expansion steel according to claim 8, characterized in that: When the intermediate billet thickness is ≤45mm, the intermediate billet is coiled and scaled through a hot coil box.

10. The method for producing 780MPa grade low-cost nano-precipitation type high hole expansion steel according to claim 5, characterized in that: In the finishing rolling process, the finishing rolling inlet temperature is controlled to be 1030-1080°C, and the final rolling temperature is controlled to be 860-900°C.